Comparative Analysis of Evolutionary Algorithms for the Optimised Beams from Thinned Concentric CAA - Kumar, B. Ashok; Kumari, E. Kusuma (Journal of Soft Computing Paradigm, 2023)
By applying proper amplitude-weighting the signals received at each element, includind the low side lobes may be gained. Aperiodic or non-uniform spacing between the components is one of the strategies and the thinned array is another strategy utilized in producing the low side lobe amplitude taper, while thinning disables some components in a uniform array. Hence optimized narrow beams are generated from concentric circular antenna arrays using both techniques i.e aperiodic spacing as well as concept of thinning to scan the entire azimuthal plane. A practical and simple antenna element is dipole and it is used for communication purpose as an array element. An extensive comparison is brought out between optimized thinned concentric circular antenna arrays and uniformly distributed fully populated concentric circular antenna array characteristics applying the and the same are presented at the end.
Keywords: Concentric CAA; Dipole Radiators; Thinning; Evolutionary Algorithms; Side Lobe Level